Evaluation of the use of vinasse as a biostimulation agent for the biodegradation of oily sludge in soil - Crivelaro, Sérgio Henrique Rezende [UNESP]; Mariano, Adriano Pinto [UNESP]; Furlan, Luis Tadeu; Gonçalves, Renato Almeida; Seabra, Paulo Negrais; Angelis, Dejanira de Franceschi de [UNESP] (Brazilian Archives of Biology and Technology, 2010)
Este trabalho objetivou estudar o efeito da vinhaça na biodegradação em solo da borra oleosa proveniente da refinaria de petróleo Replan-Petrobras. Foi utilizado o método respirométrico de Bartha para verificar a eficiência de tratamentos constituídos de solo, borra oleosa nas concentrações 7 e 14 % (m/m) e ajuste da umidade do solo com e sem vinhaça (0,11 mL/g solo seco) durante 121 dias. Embora a adição da vinhaça tenha proporcionado um aumento da população microbiana nos tratamentos, esta não se mostrou adequada para aumentar a eficiência de biodegradação da borra oleosa em solo, uma vez que não houve diferença entre o CO2 produzido nos tratamentos com ou sem vinhaça após o consumo total da vinhaça. Assim, o uso da vinhaça como agente estimulante em processos de biodegradação mostrou-se ineficiente nas condições estudadas.

This work aimed to study the effect of vinasse on the biodegradation in soil of oily sludge from the Replan-Petrobras oil refinery. The Bartha respirometric method was used to verify the efficiency of the treatments with soil, oily sludge (7 and 14% m/m) and soil moisture adjustment with or without vinasse (0.11 mL/g dry soil) for 121 days. Although an increase in the soil microbial population was obtained with the vinasse, it demonstrated not to be adequate to enhance the biodegradation efficiency of the oily sludge in soil, since there was no difference between the CO2 produced from treatments with or without vinasse after the complete consumption of the vinasse. Thus, the use of vinasse as an amendment to biodegradation processes showed not to be efficient under the studied conditions.
Keywords: biodegradation; soil; oily sludge; vinasse; landfarming